A holistic conceptual approach to concrete service life: a split into different time-stages - Castro-Borges, Pedro; Helene, Paulo (Revista ALCONPAT, 2018)
The goal of this paper is to analyze and discuss a conceptual approach that considers the holistic character of concrete service life but splits it into seven time-stages that can be compared, for understanding purposes, with those of a human being. The existing concepts about service life may be incomplete regarding those that must consider the whole life of a concrete structure. One of the reasons for this is the lack of certainty of the service life predictions which are based on models that consider a series of non-clearly defined time-stages. The life of a structure has many similarities with that of a human being. In fact, it is no coincidence that engineering has adopted some terms from the medical sciences like “pathology” to refer to structures with problems of “health”. The paper discusses the overlapping of the different time-stages as well as the reasons why the prediction models can fail.